New Technologies in the Correction of Intestinal Dysbacteriosis in Children with Recurrent Bronchitis (Global Scientific Review, 2023)
The last decades are characterized by an increase in the number of children with recurrent and chronic respiratory diseases. These phenomena are observed against the background of a general increase in the level of allergization of the child population and the number of drug complications. It should be considered a characteristic feature of the current course of the pathology of the respiratory system in patients of childhood, torpidity and duration of the course of the pathological process with the formation of atrophic and subatrophic changes in the mucous membrane of the respiratory tract. Increasingly, the transformation of recurrent respiratory diseases into chronic and severe forms is recorded. Therefore, it is necessary to further develop individualized approaches to the diagnosis, treatment and rehabilitation of sick children, with the aim of early detection of pathology and timely implementation of adequate therapeutic measures. The problem of treatment of recurrent and allergic respiratory diseases in children against the backdrop of an unfavorable current environmental situation and the development of hypoimmune conditions has become particularly relevant at the present time.